Heidi Heckelbeck and the Christmas surprise - Coven, Wanda (Coven, Wanda. Heidi Heckelbeck, 2013)
After Heidi borrows her mother's charm bracelet without permission, it gets damaged and she uses magic to try to repair it before her mother finds out, but there is a problem that only Aunt Trudy or Santa can fix.